“A fichinha de evolução é muito ultrapassada”: uma análise sobre os benefícios da implementação de softwares no CREAS (Centro de Referência Especializada em Assistência Social) - Santos, Jhenifer Cristine Sanches dos (Universidade Federal de São Carlos, 2022)
CREAS (Specialized Reference Center for Social Assistance), a medium-complexity public institution linked to the Unified Social Assistance System (SUAS), is made up of multidisciplinary teams that work to enhance the protection, strengthening of bonds and autonomy of families and individuals whose rights have been violated. There are, however, some challenges in the management of CREAS that hinder the success of interventions, such as the lack of systematization of the service and computerization of administrative-bureaucratic activities. Based on these considerations, this research aimed to analyze and understand the routine and the main challenges related to the organization and systematization of the work processes and administrative procedures of CREAS, with the purpose of evaluating the need and feasibility of computerizing the activities carried out in the institution. This was a qualitative, crosssectional study based on a case study. Through a semi-structured interview, 4 (four) higher-level technicians who worked in a CREAS located in a medium-sized city in the interior of the state of São Paulo participated in the research. The data obtained were submitted to the Content Analysis process, which resulted in four central categories: a) Description of activities; b) Records; c) Communication and work processes; d) Difficulties, challenges and recommendations. The results obtained revealed that the use of software could help in the optimization of administrative-bureaucratic activities, such as the maintenance and manipulation of medical records, preparation of reports, agenda management and case control, which could lead to more agile and efficient work processes. Furthermore, the findings of this investigation suggest that the use of software could allow for greater data security for service users.
Analysis on the benefits of implementing softwares in Reference Centers Specialized in Social Assistance Services
Keywords: Assistência Social; CREAS; Software; Desenvolvimento tecnológico; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL